Breakage of carbon nanotube agglomerates within polypropylene matrix by solid phase die drawing. Issue 4 (11th August 2020) - Lin, Xiang; Gong, Min; Innes, James; Spencer, Paul; Coates, Phil; Korde, Sachin
Abstract: Melt blending of polyolefin/carbon nanotube (CNT) composites always leads to serious agglomeration of CNTs and hence inferior properties. Thus, well‐dispersed CNTs within matrix are urgently required during processing. In this work, effective breakage of CNT agglomerates was achieved by solid‐phase die drawing at a temperature below but near to the melting temperature of the matrix. Experimental results indicate that the incurred extensional stress provides a high orientation degree on the polypropylene (PP) matrix and consequently helps rupture CNT agglomerates, leading to improved alternating current（AC） conductivity by 5–6 orders in magnitude. The reduced agglomerate ratio, the altered CNT networks (3D→2D), and the improved interfacial morphology between CNT and matrix are suggested to be responsible for the viscoelasticity variation of the composite melt and the improved property of PP/multiwalled CNTs (MWCNTs) composite. The initial loss of tensile ductility by the incorporation of MWCNTs is recovered by nearly 100%, which was attributed to the low agglomeration rate and improved interfacial morphology. This article provided the potential inspiration for the melt blending of polymer melt and CNTs. Abstract : Effective breakage of CNT agglomerates has been achieved by solid‐phase die drawing at a temperature below but near to the melting temperature of the PP matrix. This processing manipulation can further enhance the mechanical and electrical properties of composites.